2016
DOI: 10.15252/embj.201592244
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic inhibition upon CB 1 or mG lu2/3 receptor activation requires ERK / MAPK phosphorylation of Munc18‐1

Abstract: Presynaptic cannabinoid (CB1R) and metabotropic glutamate receptors (mGluR2/3) regulate synaptic strength by inhibiting secretion. Here, we reveal a presynaptic inhibitory pathway activated by extracellular signal-regulated kinase (ERK) that mediates CB1R-and mGluR2/3-induced secretion inhibition. This pathway is triggered by a variety of events, from foot shock-induced stress to intense neuronal activity, and induces phosphorylation of the presynaptic protein Munc18-1. Mimicking constitutive phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 78 publications
3
18
0
Order By: Relevance
“…We confirmed CB 1 R localization to glutamatergic (i.e., VGluT2 immunopositive [+]) terminals in the rat LPP field and then compared the effects of cannabinoid receptor agonist WIN 55,212-2 (WIN) on synaptic physiology in the S-C and LPP projections. In accord with prior work (Paton et al 1998;Schmitz et al 2016), WIN (5 μM) caused a rapid and pronounced depression of S-C fEPSPs in CA1 (P < 0.0001; Fig. 1a) that was accompanied by an increase in paired-pulse facilitation (P = 0.0067; Fig.…”
Section: Cb 1 R / Munc18-1 Signaling Is Markedly Different In 2 Hipposupporting
confidence: 91%
See 4 more Smart Citations
“…We confirmed CB 1 R localization to glutamatergic (i.e., VGluT2 immunopositive [+]) terminals in the rat LPP field and then compared the effects of cannabinoid receptor agonist WIN 55,212-2 (WIN) on synaptic physiology in the S-C and LPP projections. In accord with prior work (Paton et al 1998;Schmitz et al 2016), WIN (5 μM) caused a rapid and pronounced depression of S-C fEPSPs in CA1 (P < 0.0001; Fig. 1a) that was accompanied by an increase in paired-pulse facilitation (P = 0.0067; Fig.…”
Section: Cb 1 R / Munc18-1 Signaling Is Markedly Different In 2 Hipposupporting
confidence: 91%
“…Recent studies demonstrated that presynaptic signaling through ERK1/2 to the vesicular protein Munc18-1 is critical for CB 1 R-mediated depression of release (Schmitz et al 2016). Here, we show that CB 1 R agonists readily activate this signaling cascade at S-C synapses but not in the LPP.…”
Section: Introductionsupporting
confidence: 46%
See 3 more Smart Citations